The First Yaroslavl Summer School on Discrete and Computational Geometry - Nikolay Dolbilin; Herbert Edelsbrunner; Alexandr Ivanov; Oleg Musin (Моделирование и анализ информационных систем)
We summarize the results of the First Yaroslavl Summer School on Discrete and Computational Geometry and asses its future perspectives.